Leadership style and the employee perceived on safety climate / Syed Hazim Syed Noh - Syed Noh, Syed Hazim (Faculty of Business and Management, 2018)
Achieving several levels of performance is the objective of all organizations as this will make the organization more advanced and growing. Over the past twenty years, leadership style has become very important to most organizations today. Leadership style is very complex and is one of the major contributors to success or failure in most industries. Effective leadership style has become one of the most valuable ways to achieve employee perceived on safety climate. The purpose of this study is to assess the relationship between leadership style and the employee perceived on safety climate. In addition, this study also aims to identify which type of leadership is most likely to affect the perceived employee safety of Ramatex Textiles Industries.